Directly Emitting a High-Power Phase-Locked Laser Array by an Internal Phase Sensing System - Jinhu Long; Shuyue He; Qi Chang; Zhiqiang Gao; Yanxing Ma; Rongtao Su; Pengfei Ma; Pu Zhou (IEEE Photonics Journal)
In this article, we experimentally presented a compact, packaged high-power coherent fiber laser array based on an internal phase sensing technique. In the experiment, a laser array with three beamlets was utilized for experimental presentation. The power output of each laser channel was increased to exceed 500 W. Owing to the exceptional system design and effective thermal management, the internal phase sensing system maintained a remarkable level of performance. When the dynamic phase noise was compensated effectively by the stochastic parallel gradient descent (SPGD) algorithm, the high-power laser array was combined with phase-locked synchronization and directly emitted to the free space. When the output combined power was increased from 3 W to 1.5 kW, the phase deviation remained to be less than λ/27. In addition, the phase control error, element expansion, and further power scaling were fully discussed. This work may offer a practical reference for designing the compact, high-power fiber laser array.